Selectivity of herbicides isolated and/or with the addition of adjuvants for Physalis angulata crop - Chiconi, Leandro Aparecido [UNESP]; Bacha, Allan L. [UNESP]; Braga, Andreisa F. [UNESP]; Carrega, Willians César [UNESP]; Nepomuceno, Mariluce P. [UNESP]; Alves, Pedro Luís da C. A. [UNESP] (FapUNIFESP (SciELO), 2022)
Physalis angulata is a Solanaceae that produces fruits with a high commercial value. The interference of weeds in the cultivation of this species is one of the main factors limiting its growth. There are no herbicides registered for this crop in Brazil. Thus, the objective of this study was to evaluate the selectivity of herbicides and the use of adjuvants for the cultivation of P. angulata. We conducted three experiments: two in pots, evaluating the selectivity of the herbicides fluazifop-p-butyl, metribuzin, fomesafen + fluazifop-p-butyl, trifluralin and clethodim; and one in field conditions using the most selective herbicides from previous experiments. In the pots, we performed assessments of phytotoxicity, height, stem diameter, and total chlorophyll content every seven days up to 42 days after application. At the end of the three experiments, we evaluated leaf area, number of fruits, and dry matter of leaves, stems, and fruits. The herbicides clethodim without adjuvant and fluazifop-p-butyl are selective for P. angulata crop. Under field conditions, the application of fluazifop-p-butyl + fomesafen did not negatively affect crop production and growth, being selective to P. angulata. Metribuzin do not have the potential to be used for this crop.
Seletividade de herbicidas isolados e/ou com adição de adjuvantes para Physalis angulata
Keywords: camapu; competition; phyto-intoxication; Solanaceae; weeds